Engineering microalgae: transition from empirical design to programmable cells. (17th November 2021) - Lu, Yandu; Zhang, Xu; Gu, Xinping; Lin, Hanzhi; Melis, Anastasios
Abstract: Domesticated microalgae hold great promise for the sustainable provision of various bioresources for human domestic and industrial consumption. Efforts to exploit their potential are far from being fully realized due to limitations in the know-how of microalgal engineering. The associated technologies are not as well developed as those for heterotrophic microbes, cyanobacteria, and plants. However, recent studies on microalgal metabolic engineering, genome editing, and synthetic biology have immensely helped to enhance transformation efficiencies and are bringing new insights into this field. Therefore, this article, summarizes recent developments in microalgal biotechnology and examines the prospects for generating specialty and commodity products through the processes of metabolic engineering and synthetic biology. After a brief examination of empirical engineering methods and vector design, this article focuses on quantitative transformation cassette design, elaborates on target editing methods and emerging digital design of algal cellular metabolism to arrive at high yields of valuable products. These advances have enabled a transition of manners in microalgal engineering from single-gene and enzyme-based metabolic engineering to systems-level precision engineering, from cells created with genetically modified (GM) tags to that without GM tags, and ultimately from proof of concept to tangible industrial applications. Finally, future trends are proposed in microalgal engineering, aiming to establish individualized transformation systems in newly identified species for strain-specific specialty and commodity products, while developing sophisticated universal toolkits in model algal species. Graphical Abstract: UF0001